Axiological dominance in advertising texts: A cross-cultural linguistic analysis of the UK, Egypt, and Belarus - Mounir, Antonious Samir (Вестник Томского государственного университета. Филология)
The article presents a comprehensive axiological analysis of advertising texts across different cultural contexts. It scrutinizes linguistic and cultural factors that influence the axiological dominance in the promotional discourse. The sample materials comprise of 150 advertising texts from the UK, Egypt and Belarus. In this research, we applied the qualitative method by conducting a qualitative content analysis of advertising texts from different countries. The conceptual framework defines the core principles of axiological analysis, emphasizing the importance of cultural values in the creation of advertising content. The study suggests that the text of the ad featuring the language is a primary factor that determines the course of the values. The study is concerned with the intricate relationship between language and the transmission of values in advertising by showing the high-level and strategic competence in linguistics that is evident in the communication of values across diverse cultural and linguistic settings. There is significance to this particular study as it has undertaken an in-depth analysis of the language used in these texts deliberately to transmit specific values. Moreover, it contributes to the entire linguistic studies (from an axiological angle).